Adding vibration during varied-intensity work intervals increases time spent near maximal oxygen uptake in well-trained cyclists - Duc, S.; Urianstad, T.; Rønnestad, B. R. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Previous research suggests that the percentage of maximal oxygen uptake attained and the time it is sustained close to maximal oxygen uptake (eg, >90%) can serve as a good criterion to judge the effectiveness of a training stimulus. The aim of this study was to investigate the acute effects of adding vibration during varied high-intensity interval training (HIIT) sessions on physiological and neuromuscular responses.